The spatial structure of ocean surface temperature anomalies on the base of the accompanying measurements data on the R/V “Ak. Fedorov” in the Summer 2007-2008 - Artamonov, Yu. V.; Bunyakin, V.P.; Kislizhin, S. P.; Skripaleva, E. A. (Ukrainian Antarctic Journal, 2008)
The analysis of the spatial distribution of ocean surface temperature (SST) anomalies, calculated using the data of the accompanying hydrometeorological measurement obtained during December, 6, 2007 – March, 7, 2008 cruise of the R/V Ak. Fedorov in 53th RAE is presented in work. For an analysis were used the monthly-average SST values on 1°×1° grid (BADC HADISST dataset and gydrological World Ocean Base, 2005), array of monthly-average satellite SST values on 54x54 km grid during 1985−2002 (AVHRR Ocean Pathfinder Data JPL NOAA/NASA). It is shown that in Atlantic Ocean the positive SST anomalies were observed, which were maximal (2−2.5°C) in the West-African upwelling zone and in the latitudinal bar between the Thermal equator and 7S. In the Subantarctic and Polar zones of the South Ocean the surface temperature was also mainly higher than norm. The SST anomalies were negative to the south of Antarctic Polar front and in the Antarctic stations adjacent water areas.